2017
DOI: 10.1103/physreva.95.023608
|View full text |Cite
|
Sign up to set email alerts
|

Heisenberg-limited Sagnac interferometer with multiparticle states

Abstract: The Sagnac interferometry has been widely used to measure rotation frequency. Beyond the conventional single-particle Sagnac interferometry, we propose an atomic Sagnac interferometry via multi-particle entangled states. In our scheme, an ensemble of entangled two-state Bose atoms are moved in a ring by a state-dependent rotating potential and then are recombined for interference via Ramsey pulses after a specific time determined by the state-dependent rotating potential. The ultimate rotation sensitivity can … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 60 publications
(88 reference statements)
0
19
0
Order By: Relevance
“…[12], and was later generalized to the one with multiparticle Greenberger-Horne-Zeilinger (GHZ) state to beat the standard quantum limit (SQL) in Ref. [13]. So far, these proposed schemes were considered in ideal situations where the sensing protocols consisted of perfect unitary quantum channels.…”
Section: Introductionmentioning
confidence: 99%
“…[12], and was later generalized to the one with multiparticle Greenberger-Horne-Zeilinger (GHZ) state to beat the standard quantum limit (SQL) in Ref. [13]. So far, these proposed schemes were considered in ideal situations where the sensing protocols consisted of perfect unitary quantum channels.…”
Section: Introductionmentioning
confidence: 99%
“…Recent developments include hollow core fiber coils [31], integrated optical sources and homodyne detectors, and laser-driven FOGs that bypass the conventional requirement for temporally incoherent sources [32,33]. In addition, quantum-enhancement has recently been considered to boost rotation sensitivity [34][35][36][37][38][39][40][41], and preliminary experimental works on quantum-enhanced FOGs have demonstrated improvements via injection of squeezed vacuum [35] and entangled NOON states [39].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the entanglement in N00N states [29,30], continuous-variable squeezing [31][32][33], and optical nonlinearity [34] can enhance the sensitivity of optical gyroscopes beyond the SNL. A quantumenhanced sensitivity can also be achieved in matter-wave gyroscopes [35][36][37][38] by using spin squeezing [39][40][41] or entanglement. However, quantum gyroscopes are still at the stage proof-of-principle study and their superiority over the conventional ones in the absolute value of sensitivity still has not been exhibited [22,37].…”
mentioning
confidence: 99%